2017
DOI: 10.1016/j.scitotenv.2017.02.215
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds (VOC), formaldehyde and nitrogen dioxide (NO 2 ) in schools in Johor Bahru, Malaysia: Associations with rhinitis, ocular, throat and dermal symptoms, headache and fatigue

Abstract: • Xylene, formaldehyde and NO 2 in schools in Malaysia can be associated with fatigue among students.• Formaldehyde and NO 2 in the classrooms can be associated with ocular symptoms.• The indoor and outdoor levels of benzene were often above the EU standard for ambient air. This paper studied associations between volatile organic compounds (VOC), formaldehyde, nitrogen dioxide (NO 2 ) and carbon dioxide (CO 2 ) in schools in Malaysia and rhinitis, ocular, nasal and dermal symptoms, headache and fatigue among s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(46 citation statements)
references
References 45 publications
4
41
1
Order By: Relevance
“…In a study among students in schools in Malaysia (N = 462 pupils), formaldehyde and other selected indoor air pollutants were associated with rhinitis, ocular, nasal and dermal symptoms, headache, and fatigue. Norbäck et al (2017) arrived at similar findings. Formaldehyde was associated with ocular (p = 0.004), throat symptoms (p = 0.006) and fatigue (p = 0.001).…”
Section: Association Between Potential Health Outcomes and Chemical Hsupporting
confidence: 58%
See 1 more Smart Citation
“…In a study among students in schools in Malaysia (N = 462 pupils), formaldehyde and other selected indoor air pollutants were associated with rhinitis, ocular, nasal and dermal symptoms, headache, and fatigue. Norbäck et al (2017) arrived at similar findings. Formaldehyde was associated with ocular (p = 0.004), throat symptoms (p = 0.006) and fatigue (p = 0.001).…”
Section: Association Between Potential Health Outcomes and Chemical Hsupporting
confidence: 58%
“…The systematic review included eight studies that found associations between asthma and high levels of PM, VOC and endotoxins (Erklavec et al 2017). Norbäck et al (2017) studied associations between VOC, formaldehyde, nitrogen dioxide (NO 2 ) and CO 2 in schools in Malaysia (N = 462 pupils) and rhinitis, ocular, nasal and dermal symptoms, headache and fatigue among students. The prevalences of weekly rhinitis, ocular, throat and dermal symptoms were 18.8%, 11.6%, 15.6%, and 11.1%, respectively.…”
Section: Association Between Potential Health Outcomes and Chemical Hmentioning
confidence: 99%
“…Contamination of the internal environment with fungi and, thus, increased occurrence of SBS is mainly caused by the presence of microbiological volatile organic compounds (MVOC), which are a subgroup of volatile organic compounds (VOC)-considered to be carcinogenic-mycotoxins, fungal spores, and fragments of mycelium [58,[64][65][66][67][68]. These substances are secondary metabolites produced by fermentation and are volatile due to their physicochemical properties [69,70].…”
Section: Harmful Effects Of Microbiological Contamination On Human Hementioning
confidence: 99%
“…SBS was initially studied within office buildings and subsequently extended to residential buildings (Barmark, 2015;Smedje, Wang, Norbäck, Nilsson, & Engvall, 2017), hospitals (Gómez-Acebo et al, 2011;Vafaeenasab, Morowatisharifabad, Taghi Ghaneian, Hajhosseini, & Ehrampoush, 2014), and school buildings (Norbäck, Hashim, Hashim, & Ali, 2017;Salin et al, 2017;Takaoka, Suzuki, & Norbäck, 2015;Zhang, Li, Zhang, Zhao, & Norbäck, 2014). Office is defined as "a room or part of a building in which people work, especially sitting at tables with computers and phones, as a part of an organisation or as a part of a government department" (Office, 2018).…”
Section: Introductionmentioning
confidence: 99%